Hubungan Persepsi Petani Keramba Dengan Pemanfaatan Keberadaan Kawasan Objek Wisata Alam di Kecamatan Danau Sipin Kota Jambi - Asmaida Asmaida; Adi Putra Muhammad Ramadhan (Jurnal MeA (Media Agribisnis), 2022)
This study was conducted with the aim of describing the perception of cage farmers towards the transition of the cage business area into a natural tourism object area, describing the condition of cage farmers in the utilization of the cage business transition into a natural tourism object area, analyzing the relationship between perception and the use of the cage area into a natural tourism object area. in Lake Sipin District, Jambi City. The research was conducted in the District of Lake Sipin, Jambi City. Measurement of perception and utilization were analyzed descriptively with scoring. To see the relationship between perception and utilization, the Chi Square test was used. Withdrawal of farmer samples taken by census with a total population of 41 people. The results showed that positive perceptions of 32 FH (78.05%) and 9 FH (21.95%) farmers had negative perceptions. Based on the utilization there are 29 FHH (70.73%) having a high utilization rate and 12 FHH (29.27%) having a low utilization rate. After the Chi Square test, the value of   is 5.648, which is greater than the value of   table of 3.841, meaning that there is a relationship between the perception of cage farmers and the utilization of the existence of a natural tourist attraction in Danau Sipin District, Jambi City, with a weak positive relationship.